The Contextual Indication of admonition in the Holy Quran - آلاء هاشم جريان أ.م.د. مرفت يوسف كاظم (College of Education for Women, 2019)
Context has occupied a distinguished place as far as the understanding of the texts and deducting the rules from them or analyzing them. The context was considered as one of the important presumptions as far arriving at the desired meanings is concerned. The word is worthless and the meaning is not known unless we know the context in which it came. The context in its two types the lingual and non-lingual types. It is the best for knowing the intended meaning of the Quranic verses to know the real meaning.